Răspuns:
sper ca te am ajutat!
Explicație pas cu pas:
a)
1) ( -6 - 8 + 5 + 1 ) = -8
2) ( +3 - 9 - 2 + 4 ) = -4
3) 3 × -8 : -4 = 6
b)
1) ( +3 - 9 - 4 + 8 ) = -2
2) ( -5 + 4 - 2 + 4 ) = 1
3) -1 × -2 : 1 = 2
c)
1) ( -8 + 7 - 6 - 5 ) = -12
2) ( -3 + 9 - 1 - 4 ) = 1
3) -2 × -12 : 1 = 24
d)
1) ( +3 - 7 - 9 + 5 ) = -8
2) ( -6 - 2 + 5 + 1 ) = -2
3) -8 : -2 : 2 = 2
e)
1) - ( +8 - 2 - 5 - 9 ) = -8
2) ( -7 - 2 + 4 + 1 ) = -4
3) -8 : -4 = -2
f)
1) ( -6 + 8 - 5 - 1 ) = -4
2) ( -2 + 3 + 4 - 6 ) = -1
3) 1 + -4 : -1 = 3
g)
1) ( -8 - 3 + 2 + 7 ) = -2
2) ( +9 - 6 - 8 + 4 ) = -1
3) -3 + -2 : -1 = 5
h)
1) ( -5 - 4 + 3 + 6 ) = 0
2) ( -7 + 2 - 8 + 4 ) = -9
3) 0 : -9 = 0
i)
1) ( -2 + 8 - 9 + 1 ) = -2
2) ( -5 - 4 + 7 + 1 ) = -1
3) 5 - (-2) ÷ -1 = 4